The media agenda of the new and traditional media in Malaysia: constructing realities - Mus Chairil Samani,; Jamilah Maliki,; Mohd Helmi Abd. Rahim,; Mat Pauzi Abd. Rahman,; Normah Mustaffa, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
Mass media have always been constructing reality. Each media constructs different versions of reality which plays according to the tune of the media owners. With the rise of the new media, the reading public now has a different source of information about the existing realities. This study analyzes the different agendas of the new and traditional media. Four printed newspapers and four online newspaperswere selected for this study. A content analysis of the different media was carried. The findings indicate that the different media projects different agenda. The constructed agenda reflect the prevailing philosophy the owners of these media.